MOTIVASI BELAJAR, KEMANDIRIAN BELAJAR DAN PRESTASI BELAJAR MAHASISWA BEASISWA BIDIKMISI DI UPBJJ UT BANDUNG - Angga Sucitra Hendrayana (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2014)
This research aims to know level of learning motivation, independent learning and academic achievement Bidikmisi student scholarships at Indonesian Open University Regional office Bandung. This research is adescriptive research by taking samples of throughout Bidikmisi student scholarships at Indonesian Open University Regional Office Bandung consisting of study program in Accounting, Biology and Regional Planning City of the studentas much as 94 students at Registration Period 2013.2. The data in this study are learning motivation, independent learning, and the grade-point average (GPA). The data were analyzed descriptively to describe the level of learning motivation, independent learning, and grade-point average (GPA). The result of research shown that the average level of learning motivation are included in the category of very high. Independent learning showed that the average independent learning of students in the high category and the grade-point average (GPA) between1.75 to 3.85withan average GPAof 2.70. Penelitian ini merupakan penelitian deskriptif dengan mengambil sampel seluruh mahasiswa beasiswa Bidikmisi di UPBJJ UT Bandung yang terdiri dari program studi Akuntansi, Biologi dan Perencanaan Wilayah Kota Masa registrasi 2013.2 sebanyak 94 mahasiswa. Variabel dalam penelitian ini adalah motivasi belajar, kemandirian belajar, dan indeks prestasi belajar (IPK). Analisis data dilakukan secara deskriptif untuk mengetahui gambaran tingkat motivasi belajar, kemandirian belajar, dan IPK mahasiswa. Hasil penelitian menunjukkan bahwa motivasi belajar termasuk dalam kategori sangat tinggi, dan kemandirian belajar rata rata termasuk dalam kategori tinggi, dan IPK berada dikisaran antara 1,753,85 dengan rata-rata IPK 2,70.